(untitled) (Journal of Engineering, 2012)
The presence of heavy metals in the environment is major concern due to their toxicity. In the present study a strong acid cation exchange resin, Amberlite IR 120 was used for the removal of lead, zinc and copper from simulated wastewater. The optimum conditions were determined in a batch system of concentration 100 mg/L, pH range between 1 and 8, contact time between 5 and 120 minutes, and amount of adsorbent was from 0.05 to 0.45 g/100 ml. A constant stirring speed, 180 rpm, was chosen during all of the experiments. The optimum conditions were found to be pH of 4 for copper and lead and pH 6 for zinc, contact time of 60 min and 0.35 g of adsorbent. Three different temperatures (25, 40 and 60°C) were selected to investigate the effect of adsorption temperature on heavy metals adsorption onto Amberlite IR. The equilibrium data were analyzed by the Langmuir and Freundlich isotherms. The thermodynamic parameters such as Gibbs free energy, enthalpy and entropy changes were calculated. Moreover, in order to understand the heavy metal extraction kinetics in the presence of Amberlite IR 120, the ion exchange kinetics was also studied. The ion exchange kinetics data were regressed by the pseudo first-order, second-order models. The results obtained show that the Amberlite IR 120 strong acid cation exchange resin performed well for the removal of lead, zinc and copper.